Clinical efficacy and safety of apatinib as maintenance treatment in patients with advanced esophageal squamous cell carcinoma. Issue 12 (1st December 2020) - Liu, Guohui; Wang, Yanbo; Wang, Chunbo; He, Yunlong; E, Mingyan
ABSTRACT: Background : To investigate the clinical efficacy, safety and prognostic factors of apatinib therapy as maintenance treatment in patients with advanced esophageal squamous cell carcinoma. Methods : We selected 46 patients with advanced esophageal squamous cell carcinoma treated with radiotherapy and chemotherapy in our hospital from January 2017 to February 2019, all of whom were treated with apatinib. We analyzed the clinical efficacy, adverse reactions and prognostic factors. Meanwhile, the expression of VEGFR-2 and NF-kB was detected by the immunohistochemical SABC method. Results : The oral treatment of apatinib in the VEGFR-2 and NF-kB positive groups was better than that in the negative groups. The disease control rate was 67.39%. The main adverse reactions were hypertension (60.87%). The degree of adverse reactions was mainly grade 1-2. Cox multivariate regression analysis showed that the degree of adverse reactions and ECOG score were independent factors affecting OS in patients with advanced esophageal squamous cell carcinoma. Conclusion : The positive expression of VEGFR-2 and NF-kB is expected to be the molecular target of oral apatinib targeted therapy for esophageal cancer. Apatinib has a certain clinical effect as the maintenance treatment for advanced esophageal squamous cell carcinoma patients, with mild adverse reactions and high safety.